2019
DOI: 10.1111/ens.12387
|View full text |Cite
|
Sign up to set email alerts
|

Fruit‐ and seed‐feeding habit of the crane fly Libnotes puella (Diptera: Limoniidae) in Ryukyu Islands, Japan

Abstract: Although most crane fly larvae consume decaying plant materials and their associated microorganisms, all Libnotes species investigated so far are known to be xylophilous insects. Here we report the novel herbivorous feeding ecology of Libnotes puella. We found that L. puella larvae consumed the fruits or seeds of three unrelated plants, Mitrastemon yamamotoi (Mitrastemonaceae), Balanophora tobiracola (Balanophoraceae) and Barringtonia racemosa (Lecythidaceae). The larvae live within dense tubes formed by their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…), Metalibnotes Alexander, 1972, Neolibnotes Alexander, 1972 and Paralibnotes Alexander, 1972. Most Libnotes species are xylophilous at the larval stage and may have different preferences for wood decaying conditions ( Krivosheina 2008 , Podenas et al 2015 ), but it is also reported that L. ( L. ) puella Alexander, 1925 can be herbivorous ( Suetsugu et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…), Metalibnotes Alexander, 1972, Neolibnotes Alexander, 1972 and Paralibnotes Alexander, 1972. Most Libnotes species are xylophilous at the larval stage and may have different preferences for wood decaying conditions ( Krivosheina 2008 , Podenas et al 2015 ), but it is also reported that L. ( L. ) puella Alexander, 1925 can be herbivorous ( Suetsugu et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%